We Were Dreamers : An Immigrant Superhero Origin Story - Liu, Simu, 1989- (London : William Collins, 2022)
The star of Marvel's first Asian superhero film, Shang-Chi and the Legend of the Ten Rings, tells his own origin story of being a Chinese immigrant, his battles with cultural stereotypes and his own identity, becoming a TV star, and landing the role of a lifetime. In this honest, inspiring and relatable memoir, Simu Liu chronicles his family's journey from China to the bright lights of Hollywood with wit and humour. As a child, Simu's parents left him in the care of his grandparents, bringing him to Canada when he was four. However, Simu soon senses that his new guardians lack the gentle touch of his grandparents, resulting in harsh words and hurt feelings between him and his parents, who find their son emotionally distant and difficult to relate to. Although they are related by blood, they are separated by culture, language, and values. As Simu grows up, he plays the part of the pious child flawlessly - he gets straight As, performs exceptionally in national math competitions and makes his parents proud. However, as time passes, he grows increasingly disillusioned with the path that has been laid out for him. Less than a year out of University, he is fired from his first job and hits rock bottom. He develops a determination centred around creating his own path. This leads him to not only succeeding as an actor, but also opens the door to reconciling with his parents. We Were Dreamers is a story about growing up between cultures, finding your family, and becoming the master of your own extraordinary circumstance.
Keywords: Liu, Simu, -- 1989- -- Childhood and youth; Liu, Simu, -- 1989- -- Family; Motion picture actors and actresses -- Canada -- Biography; Children of immigrants -- Canada -- Biography; Parent and child -- Canada; Immigrants -- Canada -- Biography; Actors -- Canada -- Biography; Chinese -- Canada -- Social life and customs; Canada -- Race relations; Autobiographies